The economics of new health technologies incentives, organization, and financing - Costa-i-Font, Joan.; Courbage, Christophe; McGuire, Alistair (Oxford : Oxford University Press, 2009)
Technological change in healthcare has led to huge improvements in health services and the health status of populations. Although offering remarkable benefits, these changes often entail significant financial, physical and social risks. This text analyses the impact of advances in medical technology from an economic perspective.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical technology -- Economic aspects